2012
DOI: 10.1523/jneurosci.1054-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Control of Fear-Coping Strategies by CB1Cannabinoid Receptors

Abstract: To maximize their chances of survival, animals need to rapidly and efficiently respond to aversive situations. These responses can be classified as active or passive and depend on the specific nature of threats, but also on individual fear coping styles. In this study, we show that the control of excitatory and inhibitory brain neurons by type-1 cannabinoid (CB 1 ) receptors is a key determinant of fear coping strategies in mice. In classical fear conditioning, a switch between initially predominant passive fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 55 publications
(124 reference statements)
9
90
0
2
Order By: Relevance
“…Indeed, previous observations revealed increased interest of these conditional mutant mice in novel food or object exploration (Lafenêtre et al, 2009), but also in favoring active coping strategies, such as escape, in fear cued conditioning (Metna-Laurent et al, 2012). In the present study, when we paired cocaine selfadministration with foot shocks, GABA-CB1-KO expressed increased unconditioned and conditioned foot-shockinduced suppression of cocaine seeking.…”
Section: Deletion Of Cb1 On Gabaergic Neurons Increases the Primary Rsupporting
confidence: 55%
See 2 more Smart Citations
“…Indeed, previous observations revealed increased interest of these conditional mutant mice in novel food or object exploration (Lafenêtre et al, 2009), but also in favoring active coping strategies, such as escape, in fear cued conditioning (Metna-Laurent et al, 2012). In the present study, when we paired cocaine selfadministration with foot shocks, GABA-CB1-KO expressed increased unconditioned and conditioned foot-shockinduced suppression of cocaine seeking.…”
Section: Deletion Of Cb1 On Gabaergic Neurons Increases the Primary Rsupporting
confidence: 55%
“…When targeted genetic deletion of CB1 is applied in feeding-, novelty-, and fear-related behaviors (Bellocchio et al, 2010;Dubreucq et al, 2012;Metna-Laurent et al, 2012), deletion localized to cortical glutamatergic neurons (Glu-CB1-KO mice) produces similar effects to full CB1 blockade, apparently confirming that CB1 exclusively controls glutamatergic-dependent processes (Bellocchio et al, 2010;Dubreucq et al, 2012;Metna-Laurent et al, 2012). However, deletion of CB1 in forebrain GABAergic neurons (GABA-CB1-KO mice) is not without effect.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…enhances active responses on the expense of passive responses. Metna-Laurent et al (2012) showed that conditional CB1-KO mice show a decrease in active coping in the conditioned fear test as indicated by a delayed return to normal activity after exposure to fear-associated cues. We have shown that rats treated with URB597 disregard environmental information (e.g.…”
Section: Cannabinoids and Copingmentioning
confidence: 99%
“…It was recently suggested that endocannabinoid signaling -in addition to, or instead of regulating particular behaviors -controls coping with environmental challenges (Haller et al 2014;Haller et al 2013;McLaughlin et al 2012;Metna-Laurent et al 2012). In our studies, coping was conceptualized according to Koolhaas et al (1999) who defined active and passive coping styles as distinct behavioral phenotypes, which differ in patterns of responding upon challenge.…”
Section: Introductionmentioning
confidence: 97%